Capture enrichment of aquatic environmental DNA: A first proof of concept. (11th August 2018) - Wilcox, Taylor M.; Zarn, Katherine E.; Piggott, Maxine P.; Young, Michael K.; McKelvey, Kevin S.; Schwartz, Michael K.
Abstract: Environmental DNA (eDNA) sampling—the detection of genetic material in the environment to infer species presence—has rapidly grown as a tool for sampling aquatic animal communities. A potentially powerful feature of environmental sampling is that all taxa within the habitat shed DNA and so may be detectable, creating opportunity for whole‐community assessments. However, animal DNA in the environment tends to be comparatively rare, making it necessary to enrich for genetic targets from focal taxa prior to sequencing. Current metabarcoding approaches for enrichment rely on bulk amplification using conserved primer annealing sites, which can result in skewed relative sequence abundance and failure to detect some taxa because of PCR bias. Here, we test capture enrichment via hybridization as an alternative strategy for target enrichment using a series of experiments on environmental samples and laboratory‐generated, known‐composition DNA mixtures. Capture enrichment resulted in detecting multiple species in both kinds of samples, and postcapture relative sequence abundance accurately reflected initial relative template abundance. However, further optimization is needed to permit reliable species detection at the very low‐DNA quantities typical of environmental samples (<0.1 ng DNA). We estimate that our capture protocols are comparable to, but less sensitive than, current PCR‐based eDNA analyses.